The funeral ladies of Ellerie County : a novel - Swinarski, Claire (Avon, an imprint of HarperCollins Publishers, 2024)
"Esther Larson has been cooking for funerals in the Northwoods of Wisconsin for seventy years. Known locally as the "funeral ladies," she and her cohort have worked hard to keep the mourners of Ellerie County fed--it is her firm belief that there is very little a warm casserole and a piece of cherry pie can't fix. But, after falling for an Internet scam that puts her home at risk, the proud Larson family matriarch is the one in need of help these days. Iris, Esther's whip-smart Gen Z granddaughter, would do anything for her family and her community. As she watches her friends and family move out of their lakeside town onto bigger and better things, Iris wonders why she feels so left behind in the place she is desperate to make her home. But when Cooper Welsh shows up, she finally starts to feel like she's found the missing piece of her puzzle. Cooper is dealing with becoming a legal guardian to his younger half-sister after his beloved stepmother dies. While their celebrity-chef father is focused on his booming career and top-ranked television show, Cooper is still hurting from a public tragedy he witnessed last year as a paramedic and finding it hard to cope. With Iris in the gorgeous Ellerie County, though, he hopes he might finally find the home he's been looking for. It doesn't seem like a community cookbook could possibly solve their problems, especially one where casseroles have their own section and cream of chicken soup mix is the most frequently used ingredient. But when you mix the can-do spirit of Midwestern grandmothers with the stubborn hope of a boy raised by food plus a dash of long-awaited forgiveness--things might just turn out okay"--